Upper extremity recovery after ischaemic and haemorrhagic stroke: Part of the SALGOT study - Persson, Hanna C (Eur Stroke J, 2016)
INTRODUCTION: The purpose was to explore if there are differences in extent of change in upper extremity motor function and activity capacity, in persons with ischaemic versus haemorrhagic stroke, during the first year post stroke. PATIENTS AND METHODS: One hundred seventeen persons with stroke (ischaemic n = 98, haemorrhagic n = 19) and reduced upper extremity function 3 days after onset were consecutively included to the Stroke Arm Longitudinal Study at the University of Gothenburg (SALGOT) from a stroke unit. Upper extremity motor function (Fugl-Meyer Assessment Scale for Upper Extremity (FMA-UE)) and activity capacity (Action Research Arm Test (ARAT)) were assessed at 6 assessments during the first year; age and initial stroke severity were recorded. Differences between groups in extent of change over time of upper extremity motor function and activity capacity were analysed with mixed models repeated measurements method. RESULTS: Significant improvements were found in function and activity in both groups within the first month (p = 0.001). Higher age and more severe stroke had a negative impact on recovery in both groups. Larger improvements of function and activity were seen in haemorrhagic stroke compared to ischaemic, both from 3 days to 3- and 12 months, and from 1 month to 3 months. Both groups reached similar levels of function and activity at 3 months post stroke. CONCLUSION: Although persons with haemorrhagic stroke had initially lower scores than those with ischaemic stroke, they had a larger improvement within the first 3 months, and thereafter both groups had similar function and activity.